Apontamentos sobre a Criaç\~ao de um sistema nacional de indicadores em direitos humanos - Marco Antonio Carvalho Natalino (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The article analyses the potentialities and challenges facing the creation of a human rights system of indicators. The analysis focus on seven fundamental points. Starting with a discussion on the differences between human rights indicators and social indicators, the author presents the arguments in favor of the possibility and necessity of a human rights system of indicators. Also, the framework developed by the United Nations High Commissioner for Human Rights (UNHCHR) is discussed and some specificities of the Brazilian case are analyzed, pointing to some risks involved on the construction of a system of indicators that do not observe critically the international context at which the demand for systematic information is present. Lastly, aiming at subsidizing the construction of a national public policy for this theme, the text presents some normative, conceptual and methodological principles that would help on the construction of a system of indicators that is at the same time relevant to the multiple stakeholders, conceptually substantiated, methodologically transparent and congruent to the human rights episteme.
Keywords: I39; J15; C89; Z00; 330